PEMENUHAN UNSUR-UNSUR BERITA DALAM PEMBERITAAN COVID-19 PADA DETIK.COM - Rahayu, Ayu Tanti; Parapat, Nelson Halong (Jurnal Insani, 2022)
This research was conducted to determine how the fulfillment of news elements in Covid-19 news in online media detik.com. To answer this research problem, researchers used a journalistic theory perspective on the elements of 5W+1H news (What, Who, Why, Where, When and How). This research was conducted using qualitative research with content analysis methods. The research subject or data source in this study is the Covid-19 news on detik.com with the determination of the source using purposive sampling technique with the number of news researched as many as 12 news. The unit of analysis in this study is the sentences in the Covid-19 news script that has been broadcast on detik.com. The news sentences referred to are all sentences included in the headline, lead, body, and leg. The results of the research show that the online media detik.com has not fully implemented the elements of What, Who, Why, Where, When and How to the news under study and has not implemented journalistic discipline regarding the 5W+1H news elements which is a guideline for writing news in presenting news about the Covid-19 Pandemic.Keywords: Journalism; news; news elements; online media